Palgrave Advances in International Environmental Politics
XIV, 385 p.
Keywords: Palgrave Advances in International Environmental Politics provides a state of the art review of the major theoretical approaches and substantive debates of the field. The first section reviews the historical development of international environmental politics as well as the theoretical and methodological approaches used in its study. The following chapters each review the trajectory of a key research area within international environmental politics and elaborate on current approaches and debates. Case studies in each chapter illuminate the main theoretical questions that emerge from the review.